Xinmailong injection on left ventricular remodeling and inflammatory mediators in patients with CHF: a systematic review and meta-analysis - Xu Han; Xi Chen; Yanling Liu; Jie Yang; Wuzhi Nie; Mingjiu Yang; Xinglang Mou (Frontiers Media S.A., 2024)
Background:Chronic heart failure (CHF) is a prevalent and highly challenging cardiovascular disease associated with high mortality rates. The occurrence and progression of CHF are closely linked to left ventricular remodeling (LVR) and inflammation. Addressing LVR and reducing inflammation can significantly slow down the progression of CHF and improve patient prognosis.Objective:To evaluate the effects of Xinmailong injection (XMLI) on LVR and inflammatory mediators in CHF patients.Method:The randomized controlled trials investigating the effectiveness of XMLI treatment for CHF were retrieved from eight databases up until 31 December 2023. To evaluate the methodological quality of included studies, the Cochrane bias risk tool was employed. Furthermore, statistical analysis, sensitivity analysis, and publication bias assessment were conducted using Stata 17.0 software.Result:Compared with conventional treatment (CT), the combination therapy of XMLI and CT significantly improved LVR and reduced inflammatory mediators, mainly manifested by an increase in LVEF (MD = 6.40, 95% CI: 5.25 to 7.55, p = 0.000), a decrease in LVEDD (MD = −4.63, 95% CI: −5.69 to −3.57, p = 0.000) and LVESD (MD = −4.00, 95% CI: −5.50 to −2.50, p = 0.000), as well as a decrease in TNF-α (MD = −7.93, 95% CI: −9.86 to −6.00, p = 0.000), IL-6 (MD = −5.25, 95% CI: −6.59 to −3.92, p = 0.000), IL-18 (MD = −36.07, 95% CI: −46.76 to −25.38, p = 0.000), CRP (MD = −4.41, 95% CI: −6.40 to −2.42, p = 0.000), hs-CRP (MD = −4.90, 95% CI: −5.71 to −4.08, p = 0.000), and an increase in IL-10 (MD = 20.19, 95% CI: 10.42 to 29.97, p = 0.000). In addition, the combination therapy showed enhanced clinical efficacy (OR = 4.08, 95% CI: 3.10 to 5.37, p = 0.000), decreased expression levels of BNP (MD = −138.48, 95% CI: −155.48 to −121.48, p = 0.000), and NT-pro BNP (MD = −315.63, 95% CI: −359.25 to −272.00, p = 0.000), and increased the 6-MWD (MD = 71.02, 95% CI: 57.23 to 84.81, p = 0.000). It is noteworthy that the combination therapy did not lead to an increase in the incidence of adverse reactions (OR = 1.01, 95% CI: 0.68 to 1.50, p = 0.97).Conclusion:This systematic review and meta-analysis demonstrated the superiority of combining XMLI and CT therapies over CT alone in improving LVR and reducing inflammatory mediators in patients with CHF. Importantly, this combination therapy does not increase adverse reactions. However, it is crucial to exercise caution while interpreting the survey results due to the limited quality of the included studies.Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=492715, Identifier CRD42023492715.